INDICATIVE APPROACH TO EVALUATION THE LEVEL OF AVAILABILITY OF FINANCIAL SERVICES AS ANALYTICAL SUPPORT OF THE FINANCIAL INCLUSION INSTITUTE IN THE CONDITIONS OF FINANCIAL INSTABILITY - Khutorna, M.; Zhezherun, Yu.; Kotlyarova К. (Socio-economic relations in the digital society, 2021)
The aim of the article is to improve the indicative approach to assessing the availability of financial services. The existing approaches to the assessment of financial inclusion are studied and its components are singled out (assessment of accessibility, assessment of involvement and assessment of awareness). The stages of construction of a comprehensive indicator of the availability of financial services are systematized, which is proposed to be structured in the context of five stages, namely: identification of factors influencing the availability of financial services in the country; grouping of indicators by functional purpose; Choice of methods of information collection and evaluation of indicators; establishment of criterion values of indicators; construction of a comprehensive indicator of the availability of financial services. When calculating the availability of financial services, the need to take into account fully / partially not only indicators that cover the most important aspects of financial services supply by financial institutions, but also public demand and awareness indicators depending on the level of economic development and data constraints. It is proposed to conduct a survey to calculate these qualitative indicators. The criteria for selecting respondents for the survey are presented. A comprehensive methodology for assessing the availability of financial services based on the construction of a comprehensive indicator that characterizes the level of availability of financial services as a component of financial inclusion and includes three groups of indicators, namely: supply indicators, demand indicators and awareness indicators. Depending on the impact on the availability of financial services, each group of indicators is assigned a weight of 50%, 30% and 20%, respectively. The level of availability of financial services, depending on the value of the integrated indicator may be high, medium or low. The proposed comprehensive methodology allows to determine the procedure for calculating key indicators of availability of financial services for operational generalized assessment of financial inclusion for a certain period.